Compositional Nutrient Diagnosis (Cnd) Of Onion (Allium cepa L.) (Bangladesh Journal of Agricultural Research, 2013)
Nutritional constraints often restrict yields of crops in farmers fields. Plant nutrient status is currently diagnosed using empirically derived nutrient norms from arbitrarily defined high and low yielding subpopulations above a quantitative yield target. Generic models can assist Compositional Nutrient Diagnosis (CND) in providing a yield cutoff value between high-and lowyielding subpopulations for small databases. The objectives of the present study were to determine minimum bulb yield target of high yielding subpopulations in farmers fields and to know nutritional difference between high and low yielding subpopulations. Data were collected at random using a survey database of 42 observations from nine districts of northern region of Bangladesh where high yielding varieties of onion (cv. BARi Piaz-1) are being extensively cultivated. Nutrient composition was determined form leaf at 45-50 days after transplanting. Mean, median, minimum, maximum, standard deviations, skewness of yield as well as nutrient concentration for N, P, K, S, Ca, Mg, Na, Zn, Mn, Fe, and B were determined and a R (undetermined elements), which comprises all nutrients not chemically analyzed and quantified in onion. Row centered log ratio and cumulative variance ratio function of each nutrient was calculated. The CND generic model gave 10.61 t/ha as minimum cutoff yield of the high-yield subpopulation. Boron was identified as the core yield limiting nutrient for onion in piedmont plain, floodplain and basin soils of Bangladesh. However, S, N, P, and Zn also play a significant role for increasing bulb yield of onion. Onion in farmers fields of northern region of Bangladesh may require higher B fertilizer dose for better bulb yield. From the studied piedmont plain, floodplain and basin soils of Bangladesh, the yield limiting nutrients were established the following series: B>S>N>P>Zn>Fe>Ca>K>Mg. Bangladesh J. Agril. Res. 38(2): 271-287, June 2013 DOI: http://dx.doi.org/10.3329/bjar.v38i2.15890